The Co - Integration Analysis of Effect of Value Added Tax and Excise Duties on Economic Growth in Nigeria - Adegbite ,; Adejare, Tajudeen; Olaoye,; Olatunji, Clement (International Journal For Research In Business, Management And Accounting, 2015)
This study examined the co-integration analysis of effect of value added tax and excise duties oneconomic growth in Nigeria. It also looked at the direction of causality among value added taxexcise duty, interest rate, exchange rate and economic growth employing the method ofJohansen co-integration and the Granger causality tests using data spanning the period 1994-2014. Results showed that VAT has positive significant impact on GDP in the short run but hasnegative impact on GDP in the long run with (  = 1.296417; t=7.41; P>|t|= 0.000) and ( =-13.38159; z=-3.60 , P>|z|= 0.000) respectively. Also, VAT does not granger cause GDP. Exciseduty impacted GDP negatively in the short run but positively in the long run with (=-1.111069;t=-5.16, , P>|t|= 0.000) and ( =37.54469; z = 4.07; P>|z|= 0.000) respectively. It isrecommended that, once the value added tax impacted economic growth positively in the shortrun but negative in the long run, government should increase the rate of value added tax inNigeria, this will in turn boosting the revenue generation in Nigeria. Also, government shouldincrease excise duty on tobacco and alcoholic so as to have positive significant impact oneconomic growth in the short run.